Perbandingan Performansi Sistem ORC Dengan Varian R-216CA, R-112a, R-141b dan n-Pentane Menggunakan Aspen HYSYS - Siwan Ediamanta Perangin-angin; Sindak Hutauruk (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2021)
One of the generation systems that are widely used in various power generation industries is the Organic Rankine Cycle. This cycle has the advantage of a low evaporation point compared to the ordinary steam turbine cycle. The use of refrigerants is the key to the ORC system. Refrigerant is a fluid with quite unique characteristics and many types. This study discusses the use of various types of refrigerants used in the ORC system, namely R-216CA, R-112a, R-141b and n-pentane. By using the Aspen Hysys luna device, we can compare the performance of each Refrigerant Variant of the ORC system. With the same input parameters in each variant, namely for the incoming refrigerant temperature is 600C with a pressure of 450 Kpa, the pump exit pressure is 4000 Kpa, the results are obtained from the Pump Work, Q Condenser, Q Boiler and the resulting turbine power. The result is that the ORC system with refrigerant n-Pantene has a high value for Pump Work, Q Condenser, Q Boiler and Turbine Power produced, but when compared to performance, the System with Refrigerant with R-112a has a higher efficiency value when assessed from its performance.